The Effects of Personalized System for Instruction Learning Model on Vocational School Students’ Motivation - Ginanjar, Agi (Universitas Pendidikan Indonesia, 2019)
This study aims to determine the differences of student learning motivation using the model of learning personalized system for instruction and student learning motivation using direct instruction learning model. It used experimental research method with the randomized posttest control group design, data collecting technique of student motivation using questionnaire and for hypothesis testing using independent-samples t-test. Participants in this study were 94 vocational school students’ with a sample of 48 students, for the determination of samples using Taro Yamane formula and sampling using simple random sampling. The result of research stated that there are differences of students' learning motivation using personalized system for instruction learning model and student learning motivation using direct instruction learning model. Increasing motivation in learning physical education can use the PSI learning model. AbstrakPenelitian ini bertujuan untuk mengetahui perbedaan motivasi belajar siswa menggunakan model pembelajaran personalized system for instruction (PSI) dan motivasi belajar siswa menggunakan model pembelajaran direct instruction (DI). Metode yang digunakan dalam penelitian ini adalah metode penelitian eksperimen dengan the randomized postest-only control group design, teknik pengumpulan data motivasi belajar siswa menggunakan angket dan untuk pengujian hipotesis menggunakan independent-samples t-test. Partisipan dalam penelitian ini adalah siswa Sekolah Menengah Kejuruan sebanyak 94 orang dengan sampel sebanyak 48 orang, untuk penentuan sampel menggunakan rumus Taro Yamane dan pengambilan sampel menggunakan simple random sampling. Hasil penelitian menunjukan perbedaan motivasi belajar siswa menggunakan model pembelajaran PSI dan motivasi belajar siswa menggunakan model pembelajaran DI. Peningkatan motivasi dalam pembelajaran pendidikan jasmani dapat menggunakan model pembelajaran PSI.